Export competitiveness of Indian mushroom Industry: Present status and future prospects - Vanitha, S M; Annepu, Sudheer Kumar (Mushroom Research, 2021)
Mushrooms are increasingly considered as a high value crop, and consumer demand for mushrooms markedly expanded in the recent years. Although requiring different conditions and practices comparedwith traditional field crops, mushrooms are a viable option for the small and marginal scale growers. A mushroom farming business can be a mean of big profit in just a few weeks with considerably low startup capital investment. A person who has basic knowledge in the cultivation techniques of mushroom growing, and has an own growing yards, mushroom farming will be the perfect option for him to gain the higher profits. Realizing the health promoting benefits of mushrooms and economic returns offered by its cultivation, many new generation farmers started venturing into its business. As mushroom production is increasing constantly, more people are looking for the information on export potential of mushrooms from India. We made an attempt to collect the information from the APEDA and FAO stat to study the export competitiveness of mushrooms produced in India and discussed our observations in this paper.